Formula 2+2 : the simple solution for successful coaching - Allen, Douglas B., 1955- (Ken Blanchard series., 2004)
In today's fast-paced business environment, frequent feedback and "course correction" is absolutely vital. But about the only time most managers offer employees feedback is during scheduled (and generally infrequent) performance appraisals, which tend to be stiff, formal, and--whether intentionally or not--adversarial, and therefore ineffective. Formula 2+2 offers a simple yet powerful approach to revolutionizing feedback conversations